Предмет: Алгебра, автор: xudduux

помогите пожалуйста.​

Приложения:

Ответы

Автор ответа: SYSTEMCORE
3

\displaystyle 1)\quad (\sqrt{3})^3=\sqrt{3^3}=\sqrt{27}\quad\boxed{\times}\\\\2)\quad \frac{\sqrt{14}}{\sqrt7}=\sqrt{\frac{14}7}=\sqrt{2}\quad \boxed{\times}\\\\3)\quad(\sqrt7+1)(\sqrt7+1)=(\sqrt7)^2+2\sqrt7+1=7+2\sqrt7+1=8+2\sqrt7\quad \boxed{\times}\\\\4)\quad -(\sqrt7+1)(1-\sqrt7)=(\sqrt7+1)(\sqrt7-1)=(\sqrt7)^2-1^2=7-1=6\quad \boxed{\checkmark}

Похожие вопросы
Предмет: Математика, автор: stanislavbudash20